2004
DOI: 10.1080/02699050310001596905
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of acquired brain injury (ABI) in adults: prevalence of long-term disabilities and the resulting needs for ongoing care in the region of Flanders, Belgium

Abstract: In order to plan services for long-term care of those with acquired brain injury (ABI), the prevalence of ABI was investigated by using a postal inquiry sent to a representative sample of general practitioners, of whom 121 cooperated and registered 186 cases. The corresponding estimated prevalence of adults with ABI-related disabilities is 183 per 100 000 population. The large majority remained at home without professional assistance. One in five had resumed education or regained full employment, but over half… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 12 publications
1
29
0
Order By: Relevance
“…Previously, Lannoo et al [26] reported on the epidemiology of brain injuries in Flanders in Belgium, but this study focused on acquired brain injuries in general and not specifically on TBI. A strong feature of our study is the complete standardization of data collection over the 10-year study period and the access to raw data, permitting age-adjusted analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, Lannoo et al [26] reported on the epidemiology of brain injuries in Flanders in Belgium, but this study focused on acquired brain injuries in general and not specifically on TBI. A strong feature of our study is the complete standardization of data collection over the 10-year study period and the access to raw data, permitting age-adjusted analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term debilitating behavioural change is common regardless of injury severity [18] and while return to work is clearly a laudable aim and has an obvious economic benefit, it represents an unrealistic goal for many [19][20][21][22][23]. Indeed many brain-injured adults have no constructive means of occupying their time [24,25]. Therefore, the cost-effectiveness of rehabilitation has to be considered in the broadest terms, beyond return to work, with outcomes measured across a range of socially meaningful domains.…”
Section: Introductionmentioning
confidence: 97%
“…Stroke (cerebrovascular accident) is a form of acquired brain injury and a major cause of death and disability in the Western world [1]. Many persons who have survived a stroke experience problems in one or more health-related domains, such as physical, cognitive, behavioural and emotional well-being.…”
Section: Introductionmentioning
confidence: 99%
“…In the long term, these difficulties often lead to long-lasting problems for the financial and social well-being of the individual. As a consequence, both the health care system and the patient's social relationships, especially with the caregiver, are seriously burdened [1,2]. Many caregivers report substantial negative psychosocial sequelae and increased emotional problems, like depression, anxiety, marital problems, financial problems, low quality of life and high levels of strain [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%